1997
DOI: 10.1897/1551-5028(1997)016<0260:ccabri>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant Concentrations and Biomarker Response in Great Blue Heron Eggs From 10 Colonies on the Upper Mississippi River, Usa

Abstract: In 1993, great blue heron (Ardea herodias; GBH) eggs were collected from 10 colonies on the upper Mississippi River (UMR). They were then artificially incubated until pipping and analyzed for mercury, selenium, and organochlorines. Livers of embryos were analyzed for hepatic microsomal ethoxyresorufin-O-dealkylase (EROD) activity and four measures of oxidative stress. Brains were measured for asymmetry and blood was measured for the coefficient of variation of DNA (DNA CV). Organochlorine concentrations were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 38 publications
10
44
4
Order By: Relevance
“…Sampling of various types of feathers in these studies could explain part of these differences. PCBs and OC levels in heron eggs from the St. Lawrence River were comparable to those from other studies and lower than levels at which reproductive effects have been documented (Elliott et al, 1989;Blus, 1996;Hoffman et al, 1996;Custer et al, 1997;Thomas and Anthony, 1999). Levels of PCBs and most OCs in heron eggs declined by about one third since 1979 (Laporte, 1982), although levels of dieldrin and p,p¢-DDE from Ile du Bic appear unchanged.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Sampling of various types of feathers in these studies could explain part of these differences. PCBs and OC levels in heron eggs from the St. Lawrence River were comparable to those from other studies and lower than levels at which reproductive effects have been documented (Elliott et al, 1989;Blus, 1996;Hoffman et al, 1996;Custer et al, 1997;Thomas and Anthony, 1999). Levels of PCBs and most OCs in heron eggs declined by about one third since 1979 (Laporte, 1982), although levels of dieldrin and p,p¢-DDE from Ile du Bic appear unchanged.…”
Section: Discussionsupporting
confidence: 74%
“…Mean (standard deviation * ) concentrations of mercury in feathers (lg/g dry weight) and mercury (lg/g wet weight), total PCBs and selected organochlorines (lg/kg wet weight) in whole blood of great blue heron fledglings collected in [1996][1997] observed in blood and feather mercury levels or in PCB levels in eggs and blood (Champoux et al, 2002). Despite this decline, Hg levels in eggs were still higher or comparable to other published levels for great blue heron eggs from various locations in North America (Elliott et al, 1989;Custer et al, 1997;Thomas and Anthony, 1999). Mercury levels in blood were also high compared to other published data for nestlings of various piscivorous species (Sepuvelda et al, 1999).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Colony means of total PCBs ranged from 577 to 9,169 ppb in the current study; these values are consistent with those reported to have no observed impact on reproductive success (Custer et al 1997;Halbrook et al 1999;Harris et al 2003;Nosek and Faber 1984;Sample and Suter 1999). The dominant PCB congeners measured in the current study are similar to those reported in GBH eggs studied elsewhere (Custer et al 1997(Custer et al , 1998Harris et al 2003;Mora 1996).…”
Section: Egg Measurements and Contaminant Exposuresupporting
confidence: 90%
“…In both laboratory and field studies of birds, oxidative stress measures have been associated with Hg and selenium (Se) contamination (Custer et al, 1997(Custer et al, , 20002003a, b, 2005Hoffman and Heinz, 1998;. Chromosomal damage in birds has been associated with industrialized urban sites (Yauk and Quinn, 1996) as well as Cd exposure related to mining (Custer et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%